Discourses of Nature in New Perceptions of the Natural Landscape in Southern Chile - Aliste, Enrique; Folchi, Mauricio; Núñez, Andrés (Frontiers in Psychology, 2018)
Landscapes are shaped over time by the changing imaginaries that result from new representations of nature and the value associated with it. This paper discusses the evolving discourses which have shaped the perception of the landscape in two socially and ecologically significant contexts in Chile. The first is the central-southern region of the country, a large portion of which is now devoted to commercial forestry plantations. The second is the Patagonia-Aysén region, where since the 1990s, colonisation of a land defined by a tradition of livestock rearing has evolved into a process epitomised by the slogan “Aysén, Life Reserve”. The representation that was made of central-southern Chile in the 50 'and 60' as a deforested and degraded land was the justification for promoting a new form of land occupation: the monoculture forest, designed and executed by a specific law. Forty years on from the passing of this law, the plantations of central-southern Chile have undergone a process of naturalisation. In this case, the exaltation of nature has been permanent. The only thing that changes is the definition of nature, which ended up including forest plantations. In Patagonia-Aysén, by the other side, there has been a marked shift in the rhetoric surrounding land. This has been particularly noticeable in the case of government bodies and private ecotourism companies, which have constructed an imaginary in line with a new model of economic development for the area. In a break with tradition, both the public and private sectors are beginning to shift their investment away from agricultural and livestock exploitation and towards ecotourism and conservation projects. In both cases, we analyse the manner in which transformations in perceptions and representations of landscape bring about new forms of land use, and how new focuses of value and social interest, forged within wider environmental discourses, have brought with them unexpected social consequences, like depopulation, economic transformations, cultural changes, etc. Thus, the aim of this work is to expose and discuss the reality and scope of new green discourses and their influence on the perception of natural landscapes in the Chilean neoliberal context.